Implementasi Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin Pegawai Khususnya Aspek Jam Kerja Di Kabupaten Kutai Kartanegara - Wildan Lutfi A, Mayahayati K (Puslatbang KDOD Lembaga Administrasi Negara, 2015)
This study aims to see the implementation of Government Regulation Number 53 Year 2010 about Government Apparatus Discipline in Kutai Kartanegara regency regarding the discipline on the use of working hours. Kukar district government has followed up this regulation by issuing Regional Regulation Number 46 Year 2013 about Enforcement of Civil Servants Discipline in Kutai Kartanegara regency. Based on interviews and questionnaires on the perception of civil servants in the Kutai Kartanegara regency, it can be concluded that in some local government units, the enforcement of rules related working hours disciplines have beenoptimized at the structural level, but still not up to the lower level. Understanding on the prohibitions of Government Apparatus Discipline has been predominantly known and understood by the majority of structural officials. Management to get permission to use work hours for personal use is still tolerable but has not been managed well, and additional revenue (TPP) were deemed to be highly related to the discipline of hours worked by employees and become a powerful instrument to encourage civil servants to be discipline and obeying the rules. Coaching employees to be able to behave professionally, improve capabilities and change his mind set against the additional revenue (TPP) and working hours.Keywords: Discipline, working hours , the Government of Kutai Kartanegara RegencyKajian ini bertujuan untuk melihat implementasi PP 53 No 2010 Tentang Disiplin Pegawai di lingkungan Pemerintah Kabupaten Kutai Kartanegara pada aspek kedisiplinan terhadap jam kerja. Pemkab Kukar telah menindaklanjuti PP tersebut dengan menerbitkan Perbup No 46/2013 tentang Penegakan Disiplin PNS di lingkungan Kabupaten Kutai Kartanegara. Berdasarkan hasil wawancara dan pengumpulan kuisioner terhadap persepsi dari PNS di Pemkab Kutai Kartanegara, disimpulkan di beberapa SKPD, penegakan disiplin terkait aturan jam kerja telah optimal pada tataran struktural, namun masih belum maksimal dilaksanakan hingga ke level bawah. Pemahaman terhadap larangan-larangan dalam aturan kedisiplinan telah secara dominan diketahui dan dipahami oleh sebagian besar pejabat struktural. Pengelolaan ijin terhadap penggunaan jam kerja untuk keperluan pribadi, masih ditoleransi, namun belum dikelola dengan baik dan TPP dianggap masih sangat berkaitan dengan disiplin jam kerja pegawai dan menjadi instrumen yang ampuh untuk mendorong pegawai taat pada aturan. Pembinaan pegawai agar mampu bersikap professional, meningkatkan kapabilitasnya dan merubah mind set-nya terhadap TPP dan jam kerja.Kata Kunci : Disiplin, Jam kerja, Pemerintah Kabupaten Kutai Kartanegara